The Influence of Price, Quality of Service and Influencer Marketing on the Decision to Stay at a Villa in Badung District - Gede, Dio Widyantha; Ketut, Merta I; Komang, Asri Pratiwi (MultiTech Publisher, 2024)
This research took as its object a villa/hotel in Pecatu Village, Badung Regency, with the aim of examining the influence of price, service quality and influencer marketing on the decision to stay at a villa in Badung Regency. Quantitative Multiple Regression Research Method with a sample of 84 and data analysis using SPSS Version 24. Findings from the Research: (1) Price (X1) influences decisions to stay in a positive and significant way; (2) Service Quality (X2) influences decisions to stay in a positive and significant way; (3) Influencer Marketing (X3) influences decisions to stay in a positive and significant way; and (4) Overnight Stay (Y) influences decisions to stay in a villa or hotel in Badung Regency in a positive and significant way all at once, making them into a single unit. Research Implications This research found that the influence of price variables, service quality and influencer marketing on the decision to stay at a villa/hotel in Badung Regency is very large.